An End to Sugary Drinks: The American Academy of Pediatrics and American Heart Association Speak Out. Issue 5 (September 2019) - Beal, Judy A.
Abstract : Sugary drinks are unhealthy and should not be marketed to children and adolescents. Our pediatric nursing expert, Dr. Beal, reviews the recent statement by the American Academy of Pediatrics and the American Heart Association on public policies to reduce sugary drink consumption in children and adolescents.